Dampak Pertumbuhan Ekonomi terhadap Kemiskinan di Provinsi Sulawesi Tenggara - Muslim, Caesar; Nur, Syamsir; Hastuti; Muadsin, Ikrar (WIDA Publishing, 2024)
Poverty remains a significant issue in many regions of Indonesia, including Southeast Sulawesi (Sulawesi Utara), despite various efforts from the government and non-governmental organizations. In some cases, economic growth is not necessarily accompanied by a reduction in poverty rates. This study aims to analyze the impact of economic growth on poverty in Southeast Sulawesi Province. The data used are secondary data from the Central Statistics Agency (BPS) of Southeast Sulawesi Province, covering the period from 2013 to 2022. The analysis was conducted using simple linear regression. The results of the study indicate a positive and significant relationship between economic growth and poverty rates in Southeast Sulawesi Province, where economic growth correlates positively and significantly with the poverty rates in the region. As a result, the impact of economic growth does not help reduce poverty, but rather exacerbates it.